Designing effective stunting prevention strategies for coastal households in Bengkulu Province - Yuliantini Emy; Sukiyono Ketut; Sulistyo Bambang; Yuliarso Zulkarnain (BIO Web of Conferences)
Background: The 2023 Indonesian Health Survey reported a stunting prevalence of 21.5% nationwide, with Bengkulu Province at 20.2%. Although lower, this rate still indicates a significant public health concern, as a stunting prevalence exceeding 20% is alarming. Coastal households in Bengkulu Province are particularly vulnerable, requiring targeted strategies to address stunting through collaborative public action involving multiple factors, sectors, and stakeholders. Objectives: Efforts are focused on coastal areas to support at-risk populations, address economic disparities, and achieve sustainable reductions in stunting. Methods: This study used a descriptive design with a policy analysis approach, employing SWOT analysis to evaluate strategic factors. Both internal (strengths and weaknesses) and external (opportunities and threats) factors were analyzed to develop stunting prevention strategies. The research subjects consisted of data on stunting prevention in coastal households in Bengkulu Province during 2022–2023. Results: SWOT analysis positioned the strategy in Quadrant I, with a strength-weakness difference of 0.75 (x-axis) and an opportunity-threat difference of 0.203 (y-axis). This quadrant supports an aggressive or SO strategy, leveraging strengths to capitalize on opportunities. Conclusion: Collaborative partnerships, incorporating various factors, sectors, and actors, are crucial for designing and implementing effective stunting prevention strategies in the coastal households of Bengkulu Province.